Comparison of Teacher Competence in Agricultural Mechanics among Traditionally and Alternatively Certified Agricultural Education Teachers - Anderson, Ryan; Paulsen, Thomas H. (Journal of Agricultural Systems, Technology, and Management, 2024)
One ongoing problem in school-based agricultural education is the shortage of qualified teachers to fill vacant teaching positions (Camp, et al., 2002). With a lack of qualified candidates, school administrators have hired uncertified teachers to fill the positions (Roberts & Dyer, 2004). Prior research has shown differences between alternatively and traditionally certified school-based agricultural education teachers regarding competence in teaching agricultural concepts (Rocca & Washburn, 2006). Bandura’s (1977) theory of teacher efficacy guided this study. Teacher efficacy has been shown to positively increase motivation and levels of achievement in students when the teacher exudes a high level of efficacy (Ashton & Webb, 1986; Guskey & Passaro, 1994). The purpose of this study was to determine [STATE] school-based agricultural education teachers’ perceived levels of efficacy related to teaching agricultural mechanics skills for traditionally and alternatively certified teachers. Secondary instructors at the [STATE] Association of Agricultural Educators’ summer conference were given a paper-based survey instrument that measured their self-perceived competency in the five agricultural mechanics skill area constructs. Both the traditionally certified and alternatively certified teachers' perceived themselves most competent to teach the structures/construction construct. It should be noted that the structures/construction construct area was the only area that both traditionally and alternatively certified teachers scored between moderately competent and somewhat competent; all other construct areas were identified as moderate or lower. These findings suggest that additional in-service training for both groups should be developed and delivered in the construct areas of soil and water, electricity, and mechanics skills.